The process of Buddhist-Christian dialogue - Ingram, Paul O., 1939- (Cambridge : James Clarke & Co., 2011)
While process philosophers and theologians have written numerous essays on Buddhist-Christian dialogue, few have sought to expand the current Buddhist-Christian dialogue into a ""trilogue"" by bringing the natural sciences into the discussion as a third partner. This was the topic of Paul O. Ingram's previous book, Buddhist-Christian Dialogue in an Age of Science. The thesis of the present work is that Buddhist-Christian dialogue in all three of its forms-conceptual, social engagement, and interior-are interdependent processes of creative transformation. Ingram appropriates the categories of W.
Front cover; Half title; Title page; Copyright; Contents; List of Figures; Preface; 1. That We May Know Each Other; 2. The Structure of Buddhist-Christian Conceptual Dialogue: Christian Conceptual Dialogue with Buddhism; 3. Conceptual Dialogue with the Natural Sciences; 4. Buddhist-Christian Socially Engaged Dialogue; 5. Buddhist-Christian Interior Dialogue; 6. Creative Transformation at the Boundaries: Process and Process Thought; Bibliography; Back cover
Includes bibliographical references.
Master record variable field(s) change: 072
Keywords: Christianity and other religions -- Buddhism; Buddhism -- Relations -- Christianity; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Buddhism -- Relations -- Christianity; Christianity and other religions -- Buddhism; Christianity; Buddhism; Christianity; Interfaith relations; Electronic books